Validation of the revised Belief in a Just World Scale based on Popular Sayings - Linhares, Layanne Vieira (2022)
The development of measures that assess individual differences in the Belief in a Just World plays an important role in advancing research in this area. The intent of this article was to validate a new version of the Belief in a Just World Scale based on Popular Sayings (BJWPS), proposing that this measure may be an alternative to the original scale. For this, two studies were developed: Study 1 (N=160) aimed to presenting psychometric evidence for a new version of the BJWPS scale through an exploratory factor analysis. Study 2 (N=144) aimed to verify the goodness-of-fit of the proposed measurement model using confirmatory factor analysis. Results of the two studies indicated a single-factor structure that assesses BJW, which corroborates the theoretical frameworks of the BJW scales. Together, the results allow us to conclude that the BJWPS presented satisfactory psychometric indexes.